Immunoinflammatory Response to Acute Noise Stress in Male Rats Adapted with Different Exercise Training - Elaheh Farahbakht; Yousra Alsinani; Mohammadamin Safari; Martin Hofmeister; Rasoul Rezaie; Alireza Sharifabadi; Maryam Koushkie Jahromi (Noise and Health)
Objective: Noise pollution is a kind of stress that impairs various physiological functions. This study evaluated the effect of high-intensity interval training (HIIT) and moderate-intensity continuous training (MCT) on corticosterone, interleukin-6 (IL-6), and monocyte responses to acute noise stress in male rats. Design: Forty-two male Wistar rats were divided into seven groups, including control which was assessed at the beginning, control time which was assessed simultaneously with experimental groups (CT), HIIT, MCT, HIIT followed by noise stress (HIIT+S), MCT followed by noise stress (MCT+S), and noise stress. HIIT and MCT were performed for 8 weeks. Noise stress was induced for one session. Blood samples were taken 48 hours after the last exercise session in training and CT groups and immediately after acute noise stress in stress groups of HIIT+S, MCT+S, and noise stress. Results: In response to acute noise stress, MCT and HIIT adaptations increased corticosterone, while reduced monocytes compared to CT. MCT increased basal corticosterone and IL-6 and decreased monocytes; however, in response to acute noise stress, corticosterone was higher and monocyte count was lower in the HIIT+S group. Regarding the effect of training, corticosterone and monocytes in MCT were higher than in HIIT. The serum level of IL-6 was lower in MCT than CT group, while it was not significantly different between stress groups. Conclusion: In response to noise stress, previous exercise, especially HIIT, increased stress while did not increase inflammatory and innate immune response.